Occupational Structure of Small Towns in Haryana: 2011 - Poonam and Monika (International journal of economic perspectives, 2022)
The economic and social development of small town depends on the number of persons who are economically active, the quality of their work and the regularity of their employment. Basing our observations on the data pertaining to broad occupational categories, as per 2011census, it may be pointed out that in the urban areas of Haryana, the total workers are 6,37,020 out of which 50.34 per cent are male workers and 12.87 per cent female workers. The corresponding figures for the total workers in small towns are 2,50,686 persons, whereas the proportion of male as well as female workers is following the state pattern where male workers are 2,10,418 and female workers 40,268 of the total workers in the small towns. The intent of the present paper is to analyse the spatial patterns of the working force and its distribution in small towns of Haryana. Therefore, in the context of the above findings, the present paper attempts to identify the spatial patterns of occupational structure in Small Towns (having a population of less than 20,000) in Haryana.